Plant protein-derived anti-breast cancer peptides: sources, therapeutic approaches, mechanisms, and nanoparticle design - Zhang, Deju; Yuan, Ying; Zeng, Qingdong; Xiong, Juan; Gan, Yiming; Jiang, Kai; Xie, Ni (Frontiers in Pharmacology, 2025)
Breast cancer causes the deaths of approximately 685,000 women annually, posing a severe threat to women’s health. Consequently, there is an urgent need for low-cost, low-toxicity and effective therapeutic methods to prevent or mitigate breast cancer progression. PDBP are natural, non-toxic, and affordable substances and have demonstrated excellent anti-breast cancer activities in inhibiting proliferation, migration, and invasion, and promoting apoptosis both in vitro and in vivo, thus effectively preventing or inhibiting breast cancer. However, there are no comprehensive reviews summarizing the effects and mechanisms of PDBP on the treatment of breast cancer. Therefore, this review described the inhibitory effects and mechanisms of active peptides from different plant protein sources on breast cancer. Additionally, we summarized the advantages and preparation methods of plant protein-derived anticancer peptide-encapsulated nanoparticles and their effects in inhibiting breast cancer. This review provides a scientific basis for understanding the anti-breast cancer mechanisms of PDBP and offers guidance for the development of therapeutic adjuvants enriched with these peptides.